"Ischaemic" Colitis in Young Adults. Issue 5832 (14th October 1972) - Clark, A. W.; Lloyd-Mostyn, R. H.; Sadler, M. R. de C.
Abstract : Four cases of transient haemorrhagic colitis seen in young adults resemble 10 others in the literature. The 14 cases are distinguished from the classical transient ischaemic colitis syndrome by their youth, the low incidence of stricture formation, and the prevalence of right-sided lesions.